Level of Denture Cleanliness Influences the Presence of Denture Stomatitis on Maxillary Denture Bearing-Mucosa - Krisma, Winatty; Mozartha, Martha; Purba, Rani (UI Scholars Hub, 2014)
Plaque accumulation on internal surface of denture is a common problem among removable denture wearers. Poor denture cleanliness can increase colonization of Candida albicans and cause inflammatory reaction of denture-bearing mucosa, i.e. denture stomatitis. Objective: To find out the effect of denture cleanliness level on denture stomatitis on maxillary denture-bearing mucosa in a group of removable denture wearers who received prosthodontic treatment at Poliklinik Gigi RSMH Palembang and to investigate the denture hygiene habits of removable denture wearers. Methods: Thirty subjects participated in this study. Denture cleanliness level was assessed with disclosing solution to disclose denture plaque on internal surface of maxillary denture. Cleanliness level was graded according to Budtz-Jorgensen. Intraoral examination was done to determine any visible signs of denture stomatitis. Data referring to denture hygiene habits of removable denture wearers was collected from interview using questionnaire. Data were analyzed using the Komolgorov-Smirnov test. Results: Result of the study showed that 40% subjects had poor upper denture cleanliness. Denture stomatitis was observed on maxillary denture-bearing mucosa in 43.3% subjects. Kolmogorov-Smirnov test showed that there was a significant effect of denture cleanliness level on denture stomatitis on maxillary denture-bearing mucosa (p